An assessment of static and dynamic balance effectiveness in one-leg stance of young footballers - Andrew Rinaldi Sinulingga; Inese Pontaga; Kristaps Slaidiņš (Termedia Publishing House, 2024)
Purpose Balance allows multidirectional lower limb movements that improve technical football skills and reduce injury caused by match activities. This study aimed to evaluate the static and dynamic balance of preferred and nonpreferred legs during unipedal stance in young footballers and investigate correlations between the two types of balance across each parameter. Methods Forty-three youth players (mean age = 15.81 ± 1.33 years, height = 179.50 ± 6.14 cm, body mass = 69.73 ± 9.35 kg) were involved in this study. Static balance was assessed via ellipse area (EA), perimeter length (P), anterior-posterior deviation (APD), medial-lateral deviation (MLD), trunk deviation (TD), average anterior-posterior speed (AAPS), and average medial-lateral speed (AMLS). The total stability index (TSI) and trunk total deviation (TT D) dynamic parameters were also examined. Results None of the static balance parameters showed significant differences between standing on the preferred and nonpreferred legs. Similarly, no meaningful distinctions were observed between the preferred and nonpreferred legs in terms of dynamic balance parameters. Overall, static and dynamic balances indicated no correlation, although minor connections were found between parameters: TT D and EA (r = 0.332; p = 0.03), TT D and MLD (r = 0.335; p = 0.02), and TT D and TD (r = 0.423; p = 0.01) Conclusions The balance evaluation in young football players should incorporate dynamic and static assessments because the postural control outcomes in these two tasks are independent. Participants underwent testing for both static and dynamic balance, revealing no noticeable differences between their preferred and nonpreferred legs.